Lasting alteration of spatial orientation induced by passive motion in rabbits and its possible relevance to mal de débarquement syndrome - Maruta, Jun (Frontiers in Neurology, 2023)
Background Mal de débarquement syndrome (MdDS) is a chronic disorder of spatial orientation with a persistent false sensation of self-motion, whose onset typically follows prolonged exposure to passive motion of a transport vehicle. Development of similar but transient after-sensations mimicking the exposed motion and associated postural instability, indicative of central vestibular adaptation, are common. The cause of MdDS is thought to be a subsequent failure to readapt to a stationary environment. However, vestibular plasticity pertinent to this illness has not been studied sufficiently. Because the rabbit's eye movement is sensitive to three-dimensional spatial orientation, characterizing maladaptation of the vestibulo-ocular reflex (VOR) induced in the animal may open an approach to understanding MdDS. Methods Three rabbits underwent a series of 2-h conditioning with an unnatural repetitive motion that involved a complex combination of roll, pitch, and yaw movements in a head-based reference frame, consisting of periodic rolling in darkness in a frame of reference that rotated about an earth-vertical axis. Eye movement in three dimensions was sampled during the conditioning stimulus as well as during test stimuli before and up to several days after conditioning. Results During roll-while-rotating conditioning, the roll component of the VOR was compensatory to the oscillation about the corresponding axis, but the pitch component was not, initially prominently phase-leading the head pitch motion but subsequently becoming patently phase-delayed. Unidirectional yaw nystagmus, weak but directionally compensatory to the earth-vertical axis rotation, was seen throughout the period of conditioning. After conditioning, simple side-to-side rolling induced an abnormal yaw ocular drift in the direction that opposed the nystagmus seen during conditioning, indicating a maladaptive change in spatial orientation. The impact of conditioning appeared to be partially retained even after 1 week and could be partially reversed or cumulated depending on the rotation direction in the subsequent conditioning. Conclusion The observed reversible long-term maladaptation of spatial orientation as well as the depth of knowledge available in relation to the vestibular cerebellar circuits in this species support the potential utility of a rabbit model in MdDS research.